Farm Animal Veterinarians’ Knowledge and Attitudes toward Antimicrobial Resistance and Antimicrobial Use in the Republic of Serbia - Jovana Vidović; Dragica Stojanović; Petra Cagnardi; Nebojša Kladar; Olga Horvat; Ivana Ćirković; Katarina Bijelić; Nenad Stojanac; Zorana Kovačević (Antibiotics, 2022)
Antimicrobial resistance (AMR) is considered one of the most prevalent global health issues in both veterinarian and human medicine. This complex problem requires a “One Health” approach with the cooperation of all healthcare sectors, as well as agriculture, finance, and consumers. We conducted a survey with the objective to assess the knowledge and attitudes of farm animal veterinarians toward AMR and antimicrobial use in the Republic of Serbia with a small focus on mastitis therapy. A total of 110 respondents completed the questionnaire, which represents a response rate of 27.3%. The majority of our respondents (n = 102, 92.7%) completely agreed that AMR currently represents severe concern in the health sector. Unfortunately, less than one-third (n = 34, 30.9%) of the respondents had only heard about antimicrobial stewardship. Participants showed a positive attitude toward prudent antimicrobial use and were open to solutions to the AMR crisis. We noticed a certain gap between farm veterinarians’ desire to improve and perform better in daily practice, while at the same time feeling like they did not have enough guidance, help, and resources.